Poza kategoriami – na przecięciu teorii feministycznych i queerowych - Lewińska, Karolina (Acta Neophilologica, 2024)
Queer theory assumes that identity cannot be crystallized, which may seem contradictory to feminism, rooted in a distinction between cultural and biological sex and centered on women's identity. The aim of the article is to outline the network of connections between both concepts, paying particular attention to the issue of the feminist subject. A review of the mentioned theories may become the basis for reflection on the benefits of combining feminist and queer perspectives in literary studies. Considering the category of femininity in queer research allows for filling the gaps created by the marginalization of non-heteronormative heroines and writers.